HUBUNGAN KINERJA MENGAJAR DOSEN DAN LINGKUNGAN BELAJAR DENGAN MOTIVASI BELAJAR MAHASISWA TEKNIK ELEKTRO FAKULTAS TEKNIK UNIVERSITAS PANCA MARGA PROBOLINGGO - Linda Kurnia Supraptiningsih (STKIP PGRI TULUNGAGUNG, 2018)
This study aimed to analyze correlation of teachers’ teaching performance and learning environment with students’ learning motivation. The population was 114 students of Electrical Engineering Major Faculty of Engineering Panca Marga University Probolinggo. The respondents were 89 students was choosen by purposive random sampling. The method used in this research is descriptive and inferential analysis method with multiple regression. The results showed a positive and significant correlation (0,716) of teachers' teaching performance and learning environment simultanousely to students' motivation.